2002
DOI: 10.1074/jbc.m202430200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the N-terminal Region of the Phage GA-1 Single-stranded DNA-binding Protein for Its Self-interaction Ability and Functionality

Abstract: The single-stranded DNA-binding protein (SSB) of phage GA-1 displays higher efficiency than the SSBs of the related phages 29 and Nf. In this work, the selfinteraction ability of GA-1 SSB has been analyzed by visualization of the purified protein by electron microscopy, glycerol gradient sedimentation, and in vivo crosslinking of bacterial cultures infected with phage GA-1. GA-1 SSB contains an insert at its N-terminal region that is not present in the SSBs of 29 and Nf. Three deletion mutant proteins have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In line with the results of the Y2H Bam35 intraviral interactome [65], where no self-interaction of this protein was observed, B35SSB is a monomer in solution. The podoviral Φ29SSB and Nf SSBs are also monomers but GA-1 SSB is generally a hexamer in solution, although at high salt concentration (200 mM NaCl) it is detected as a monomer [66]. Although a similar salt concentration was used in our ultracentrifugation assays, a lower concentration was used in the crosslinking assays, confirming the monomeric state of B35SSB regardless of the salt concentration.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In line with the results of the Y2H Bam35 intraviral interactome [65], where no self-interaction of this protein was observed, B35SSB is a monomer in solution. The podoviral Φ29SSB and Nf SSBs are also monomers but GA-1 SSB is generally a hexamer in solution, although at high salt concentration (200 mM NaCl) it is detected as a monomer [66]. Although a similar salt concentration was used in our ultracentrifugation assays, a lower concentration was used in the crosslinking assays, confirming the monomeric state of B35SSB regardless of the salt concentration.…”
Section: Discussionmentioning
confidence: 71%
“…In some cases, such as GA-1 and T4 SSBs, the N-terminal domain has a role in cooperativity through self-association mediated by electrostatic interactions [66,69]. Nevertheless, within the C-terminal region of B35SSB, we have identified two conserved positively charged residues, K130 and K156, whose non-conservative mutation severely affects the ssDNA-binding ability.…”
Section: Discussionmentioning
confidence: 98%
“…Φ29 protein p5 is a single-stranded DNA binding protein (Martin et al, 1989 ) that protects DNA from nucleases (Martin et al, 1989 ) and prevents unproductive binding of Φ29 DNAP to ssDNA generated during replication (Gutiérrez et al, 1991 ). Φ29 SSB has high sequence similarity with SSBs from the related podoviruses Nf and GA-1, although Φ29 and Nf are monomeric in solution, whereas GA-1 SSB is hexameric (Soengas et al, 1995 ; Gascón et al, 2000a ), by means of a N-terminal additional motif (Gascón et al, 2002 ). Podoviral SSBs share some key hydrophobic residues with unrelated viral SSBs (Gutiérrez et al, 1991 ) and, indeed, they may also share the SSBs common OB-fold, as found by secondary structure prediction and multiple sequence alignment (Figure 9 ).…”
Section: φ29 Protein P5 the Viral Single-stranded Dna Binding Proteimentioning
confidence: 99%
“…It contains an insert at its N-terminal region which is not present in ø29 gp5, and self-interacts and forms filamentous structures similar to ø29 gp1 (Gascón et al, 2000a(Gascón et al, , b, 2002. Biochemical study using N-terminal deletion mutants of GA-1 SSB showed that the N-terminal insert was important for the self-interaction, the effective binding to ssDNA, and the stimulatory effect on viral DNA replication in vitro (Gascón et al, 2002). In the N-terminal region of GA-1 SSB, a KDYIKVY sequence was especially important because the deletion of this region diminished the functionality of the GA-1 SSB (Gascón et al, 2002).…”
mentioning
confidence: 99%
“…Biochemical study using N-terminal deletion mutants of GA-1 SSB showed that the N-terminal insert was important for the self-interaction, the effective binding to ssDNA, and the stimulatory effect on viral DNA replication in vitro (Gascón et al, 2002). In the N-terminal region of GA-1 SSB, a KDYIKVY sequence was especially important because the deletion of this region diminished the functionality of the GA-1 SSB (Gascón et al, 2002). We found that the KDYIKVY sequence is almost perfectly conserved in the C-terminal region of ø29 gp1 (Fig.…”
mentioning
confidence: 99%